2001
DOI: 10.1677/joe.0.1700185
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the mouse sodium iodide symporter and its expression in the mammary gland and other tissues

Abstract: Iodide concentration in milk by mammals is a necessary step for thyroid hormone synthesis by the newborn. With the purpose of using the mouse as an animal model to analyse the role of the sodium iodide symporter (NIS) in iodide transport and its regulation in the mammary gland, mouse NIS (mNIS) cDNA was isolated from lactating mice. The cloned sequence shows an open reading frame of 1854 nucleotides encoding a protein of 618 amino acids highly homologous to the rat and human NIS (95% and 81% identity respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 38 publications
(58 reference statements)
6
58
0
2
Order By: Relevance
“…In this study, we used the mouse NIS identified by Perron et al (2001). Its sequence and known functional properties are similar to those of its rat counterpart (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used the mouse NIS identified by Perron et al (2001). Its sequence and known functional properties are similar to those of its rat counterpart (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis, plasmids, and cDNA construction of His-tagged and chimeric NIS The mouse NIS (mNIS) coding region was subcloned into pcDNA3.1 (Invitrogen) as described previously (Perron et al 2001). The full-length human NIS (hNIS; a generous gift of Prof. S M Jhiang) was inserted between the BamHI and XhoI sites of the pcDNA5 FRT plasmid (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that NIS expression is also induced in the mammary gland during lactation (3,22,23). Iodide uptake was also detected in nonlactating mammary glands in particular cases (24).…”
Section: Introductionmentioning
confidence: 98%
“…The rat NIS sequence was the first to be identified (1) followed by the human (2) and mouse sequences (3). NIS (also called SLC5A5), a member of the sodium/solute symporter family, is an integral membrane protein that resides in the basolateral membrane of thyroid epithelial cells (for review see (4)).…”
Section: Introductionmentioning
confidence: 99%